Прогнозування розвитку газової промисловості в умовах ринкових та екологічних обмежень - Kostyukovskyi B.A.; Leshchenko I.Ch. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
Principles of construction and formalization for basic dependences of optimization model are resulted for gas industry development prognostication. They take into account the features of market economy and requirement to minimization of negative influence on an environment in accordance with the international nature protection obligations of Ukraine.